Message, Messages - Jackson, Kenneth David (Pessoa Plural)
PESSOA, Fernando (2022). Message. Edited by Jerónimo Pizarro. Short Reading Guide by António Cirurgião. Translated by John Pedro Schwartz and Robert N. Schwartz. Lisbon: Tinta-da-China. 183 pp. [ISBN: 978-989-671-695-0]